1999
DOI: 10.1021/jm980348t
|View full text |Cite
|
Sign up to set email alerts
|

Orally Active Isoxazoline Glycoprotein IIb/IIIa Antagonists with Extended Duration of Action

Abstract: Modification of the alpha-carbamate substituent of isoxazoline GPIIb/IIIa (alphaIIb beta3) antagonist DMP 754 (7) led to a series of alpha-sulfonamide and alpha-sulfamide diaminopropionate isoxazolinylacetamides which were found to be potent inhibitors of in vitro platelet aggregation. Aryl- and heteroaryl-alpha-sulfonamide groups, in conjunction with (5R)-isoxazoline (2S)-diaminopropionate stereochemistry, were found to impart a pronounced duration of antiplatelet effect in dogs, potentially due to high affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The difference in platelet dissociation rate appears to be responsible for the duration of in vivo antiplatelet efficacy. XR299 demonstrated sustained antiplatelet efficacy when given three times a day in canine platelets ( Mousa et al ., 1998d ), Roxifiban when given QD in baboon platelets ( Mousa et al ., 1998b ), and DMP802 when given once a week in baboon platelets ( Mousa et al ., 1998e ; Olson et al ., 1997 ). Roxifiban active form demonstrated high potency in inhibiting platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in platelet dissociation rate appears to be responsible for the duration of in vivo antiplatelet efficacy. XR299 demonstrated sustained antiplatelet efficacy when given three times a day in canine platelets ( Mousa et al ., 1998d ), Roxifiban when given QD in baboon platelets ( Mousa et al ., 1998b ), and DMP802 when given once a week in baboon platelets ( Mousa et al ., 1998e ; Olson et al ., 1997 ). Roxifiban active form demonstrated high potency in inhibiting platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Roxifiban, an α‐carbamate substituted isoxazoline analogue demonstrated tight binding and slow dissociation rate from human platelet ( Mousa et al ., 1998a ) as compared to non‐α carbon substituted analogue, XR299 ( Mousa & Wityak, 1998 ; Wityak et al ., 1997 ). Furthermore, α‐substitution with sulfonamide resulted in an even slower platelet dissociation rate ( Olson et al ., 1997 ). Structure activity relationship within the isoxazoline Roxifiban series showed that substituent at the α‐carbon next to the carboxy terminal represent an exosite for the tight binding to human platelets leading to slow platelet dissociation rate ( Mousa & Wityak, 1998 ; Xue et al ., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More intriguingly, changing the solvent to acetonitrile led to the formation of 2-trifluoroacetyl nitrosoarenes and their hydrates as the major products. Molecules containing the isoxazoline core are found to exhibit significant antiplatelet activity. , These types of molecules also exhibit insecticidal properties; Afoxolaner and Fluralaner are commercial drugs used to treat fleas in mammals (Scheme ). , Nitroso compounds serve as reactants for various synthetic transformations such as those involving nitroso aldol reactions, ene reactions, cycloaddition, etc .…”
Section: Results and Discussionmentioning
confidence: 99%
“…13 For all in vitro studies, XP280, the salt of the active, free acid form of the prodrug roxifiban was employed. 19 …”
Section: Miscellaneousmentioning
confidence: 99%